Urgent considerations for assessment of coma in the emergency department - Aldarwish, Tammam Mozher; Alolowi, Talal Hussain; Alsadiqi, Rayan Othman; Al Hassan, Hussain Ali; Alqahtani, Abdullah Saeed; Hammad, Ahmed Mohammed Al; Almalki, Wafa Mohammad; Zara, Jawad Mubarak Al; Alshahrani, Saud Dhafer; Alyami, Bashayer Ali; Alotaibi, Ahmed Hamoud (International Journal Of Community Medicine And Public Health, 2021)
Not speaking, closed eyes, absent response to tactile, verbal or noxious stimuli are characteristic of comatose patients. Many causes of coma have been identified and reported in the literature. However, other causes might require extensive assessment and evaluation approaches. The attending physicians start with the baseline support of life for the affected patients, followed by rapid assessment and evaluation of the etiology and pathophysiology and adequate physical examination. In addition, it requires imaging and laboratory investigations whenever needed to determine the most appropriate management plan. In this literature review, we have conducted a brief discussion about the urgent considerations for the assessment of coma in the emergency department. Many causes can attribute to the development of coma. Therefore, adequate assessment and evaluation is a key component in the management of the affected patients in the emergency department. Moreover, the management approach might differ based on the underlying etiology. Nevertheless, caring for breathing, circulation, management of the airways, and stabilization are the main steps that should be done for each comatose patient. Physical examination is also critical in such situations, where imaging or conducting laboratory tests might not be suitable for some patients. Finally, the treatment plan should be directed based on the underlying etiology of coma.